2005
DOI: 10.1016/j.physe.2005.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Electron wave functions on in a static magnetic field of arbitrary direction

Abstract: A basis set expansion is performed to find the eigenvalues and wave functions for an electron on a toroidal surface T 2 subject to a constant magnetic field in an arbitrary direction. The evolution of several low-lying states as a function of field strength and field orientation is reported, and a procedure to extend the results to include two-body Coulomb matrix elements on T 2 is presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
(39 reference statements)
0
20
0
Order By: Relevance
“…Here the latter approach will be adopted in order to facilitate comparisons to a related work [6] and because of the ease by which the Hamiltonian matrix elements…”
Section: Numericsmentioning
confidence: 99%
See 3 more Smart Citations
“…Here the latter approach will be adopted in order to facilitate comparisons to a related work [6] and because of the ease by which the Hamiltonian matrix elements…”
Section: Numericsmentioning
confidence: 99%
“…Nanostructures with novel geometries have become the subject of a large body of experimental and theoretical work [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23]. Many of the fabricated structures exhibit curvature on the nanoscale making once purely theoretical investigations of quantum mechanics on curved and reduced dimensionality surfaces relevant to device modelling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These facts allow us to manipulate the Coulomb interaction between particles and the Aharonov-Bohm (AB) [3] oscillations. In spite of the simplest model used to describe ring-like devices and quantum interference effects being based on one-dimensional rings [4][5][6], experimental studies [7] and theoretical calculations [8,9] with only one electron in a single toroidal QR [8] or concentric toroidal QRs [9] have revealed that the energy spectrum is strongly dependent on the shape and size of the QRs. The one-particle energy spectrum has been calculated by using the diagonalization method [8,9], while the energy structure of neutral and charged donors in a toroidal QR have been analyzed by using the variational method [10] or adiabatic approximation [11].…”
Section: Introductionmentioning
confidence: 99%